Factors Influencing Student Activeness in Religious Extracur-ricular Activities at State Elementary School 3 Katobengke, Baubau City - Adi, Muh. Yudi Prasetya; Rahim, Abdul; Maudin, Maudin (Insan Akademika Publications, 2025)
This study aims to analyze the factors that influence student activity in religious extracurricular activities at SD Negeri 3 Katobengke and the impacts they cause. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research sample consisted of 166 respondents, including the principal, supervising teachers, and students in grades IV-VI who participated in religious extracurricular activities. The results of the study indicate that student activity is influenced by internal and external factors. Internal factors include personal motivation and student interest in religious activities, while external factors include parental support, the role of teachers and supervisors, the school environment, and peer influence. As many as 55% of students are classified as active, 30.2% are quite active, and 14.8% are less active in participating in these activities. Student activity in religious extracurricular activities has a positive impact, such as increasing religious awareness, discipline, and strengthening social relationships.